Synthesis, detection, and quantification of modified nucleotides in RNA - Baron, Francis (2020)
Background: N6-methyladenosine (m6A) is the most abundant internal modification of mRNA. m6A regulates almost every stage in the mRNA life cycle with essential roles in splicing, polyadenylation, nuclear export, stability, translation, and degradation. m6A is essential for normal development of eukaryotic organisms, and abnormal levels of m6A have been associated with the development of disease including various types of cancer. Many research groups are working on artificially manipulating m6A levels for the therapeutic treatment of disease.